PEMBERDAYAAN KOMUNITAS BANK SAMPAH DI BOJONEGORO MELALUI PELATIHAN PEMBUATAN ECOBRICK - Nila Dwi Susanti; Eryul Mufidah; Aris Zulianto (LP2M Universitas Ibrahimy, 2023)
The formulation of the problem taken by researchers in this community service activity is how to provide knowledge and insight about plastic waste processing to the community by empowering the Bojonegoro waste bank community, and how to make ecobricks and develop creative products to reduce non-organic waste in the waste bank community. In Bojonegoro? This community service uses the (ABCD) asset-based community development method, which utilizes used goods and trash that are around that are owned by villagers and then used as material that empowers the waste bank community in Bojonegoro. In the (ABCD) method, asset-based community development has several steps in its implementation and for conducting research, namely discovery, dream, design, define and destiny. Based on the results of community service, it can be concluded as follows: How to make ecobricks using plastic waste by collecting the waste, then cutting it. After that, the bottles are filled with plastic until they are solid and then stacked into bricks. Apart from that, ecobricks can be educational tools such as educational game tools (APE) from ecobricks, and puzzle learning media from ecobricks.